Performance analysis of IRS aided downlink NOMA short-packet communication with hardware impairment - Lei YUAN; Jing XU; Mingxiu MO; Yan LEI (Tongxin xuebao)
Impact of hardware impairment on the performance of intelligent reflecting surface (IRS) aided downlink two-user short-packet communication (SPC) systems using non-orthogonal multiple access over Rician channels was analyzed.Phase adjustments at the IRS were based on statistical channel state information.Firstly, the analytical expressions for average block error rates of two users were derived by using central limit theorem, moment matching method, SPC related theory, and Gaussian-Chebyshev quadrature method.Secondly, to minimize the transmission latency under the reliability constraints of two users, the optimal power allocation scheme for the considered system was given by using the proposed bisection search algorithm and one-dimensional search algorithm.Finally, simulation results verified the correctness of the theoretical analysis and showed that, compared to long-packet communication, hardware impairments have a greater impact on SPC.